PENGARUH PENGUNAAN MEDIA SOSIAL DAN INTERAKSI SOSIAL TERHADAP PEMBENTUKAN BUDAYA ALONE TOGETHER PADA SEKAA TRUNA DESA KESIMAN PETILAN , KECAMATAN DENPASAR TIMUR KOTA DENPASAR: PENGARUH PENGUNAAN MEDIA SOSIAL DAN INTERAKSI SOSIAL TERHADAP PEMBENTUKAN BUDAYA ALONE TOGETHER PADA SEKAA TRUNA DESA KESIMAN PETILAN , KECAMATAN DENPASAR TIMUR KOTA DENPASAR - Ni Kadek Ayu Pradnya Paramita; I Nyoman Yoga Segara; Ida Ayu Tary Puspa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The influence of globalization cannot be denied because it is a sign of the emergence of a new era that entails socio-cultural changes in society. This study includes descriptive quantitative research that may raise questions, namely: regarding the use of social media, which in this study was limited to WhatsApp (WA) platforms only. ). ), Instagram (IG) and Facebook (FB) and social interaction on Sekaa Teruna in Kesiman village, eastern district of Denpasar Denpasar city. The problems encountered in this area are all related to the use of social networks, in particular there are still many teenagers who cannot separate the usefulness of social activities and Sekaa Teruna's activities. Sekaa Teruna's dating act. The population of this study included members of Sekaa Teruna, Kesiman Petilan Village, East Denpasar District, Denpasar City. In this study, the sampling technique used is probability sampling. The sample size used in this study was 92 members of the Sekaa Teruna in Kesiman Petilan Village, East Denpasar District, Denpasar City. The data analysis technique used in this study is multiple regression analysis. According to the results of the study, social media has a significant influence on Alone Together Culture. Social interaction has a significant effect on Alone Together Culture. Social media and social interaction simultaneously influence one's culture with an adjusted r-squared value of 0.431, which means influence of social media and social interaction for Alone Together Culture (Y) is 43.1% and the remaining 56.9% is affected by other factors. as research variables.